OP0062 The Addition of One or More Biologics to Methotrexate in Children with Juvenile Idiopathic Arthritis Increases the Incidence of Infections and Serious Adverse Events. The 5882 Pharmachild Cohort. (9th June 2015) - Swart, J.; Pistorio, A.; Bovis, F.; Alekseeva, E.; Hofer, M.; Nielsen, S.; Anton, J.; Consolaro, A.; Panaviene, V.; Stanevicha, V.; Trachana, M.; Ailioaie, C.; et al.
Abstract : Background: Treatment of juvenile idiopathic arthritis (JIA) has greatly changed in the past 15 years thanks to the introduction of biologic agents but little is known on the long-term safety profiles. Objectives: To evaluate the long-term safety profile of a large cohort of JIA patients treated with methotrexate (MTX) alone or in combination with one or more biologic agents in the Pharmachild registry. Methods: Pharmachild is an ongoing, multicenter, non-interventional, retrospective/prospective observational registry of patients with JIA treated with either MTX alone or in combination with one or more biologic agents as part of their standard clinical care. 3 treatment groups of patients were considered: treated with MTX only, treated with MTX+1 biologic agent (MTX+1B) and treated with MTX+>1 subsequentially given biologic agent (MTX+>1B). Safety was re-coded by certified assessors according to the Medical Dictionary for Regulatory Activities (MedDRA). True incidence rate events' 100 patient-years (PY) for events at least moderate other adverse events (AE) including events of special interest (ESI) or were calculated for all MedDRA System Organ Class (SOC). Results: Out of 5882 JIA patients: 1715 (29%, 3832 PY, median disease duration, DD, 2.9 years) treated primarily with MTX (no biologics), 3007 (51%, 7013 PY, DD 4.7 years) treated with MTX+1B (67% etanercept, 18% adalimumab, infliximab/tocilizumab 5% each) and 1117 (19%, 4892 PY, DD 7.1 years) treated with MTX+>1B (31% etanercept, 27% adalimumab, 15% infliximab, 9% tocilizumab). 2355 (40%) children were treated also with corticosteroids (82% in systemics) and 1176 (20%) with other DMARDS. There were 609 (10.4%) systemic, 1195 (20.3%) oligo persistent, 2914 (49.5%) extended/poly RF pos or neg and 1164 (19.8%) other JIA categories. The incidence rates (Table ) of serious AE increases with the addition of ≥1 biologic agents (2.1, 3.2, 8.9). A similar trend was observed for infections (3.2, 3.3, 4.4); serious infections rates were 0.5, 1, 1.9 respectively. The incidence rates for varicella were 0.55, 0.34, 0.41 and for herpes zoster 0.08, 0.24, 0.51 in the 3 groups, respectively. Incidence rates for injury, poisoning and procedural complications, blood and lymphatic system, eye and other were higher in the group treated with more than 1 biologic agent. Incidence rates for gastrointestinal and hepatobiliary disorders were higher for the MTX only group when compared to the other 2. Patients who discontinued the MTX or biologics for AE or drug intolerance were 75 (4%), 483 (16%) and 210 (18%). There were a total of 4 malignancies (2 acute lymphocytic leukemia, 1 thyroid cancer, 1 fibroadenoma of breast). There were 12 deaths (1, 5 and 6 in each of the 3 groups). Conclusions: The introduction of one or more sequential biologic agent increase the rate of serious adverse events, infection when compared to the treatment with MTX alone. Disclosure of Interest: J. Swart: None declared, A. Pistorio: None declared, F. Bovis: None declared, E. Alekseeva Grant/research support from: Roche, Abbott, Pfizer, Bristol-Myers Squibb, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Bristol Myers Squibb, Medac, Novartis, Pfizer, M. Hofer: None declared, S. Nielsen: None declared, J. Anton Grant/research support from: Pfizer, abbvie, Novartis, Roche and Sobi, Speakers bureau: Pfizer, abbvie, Novartis, Roche and Sobi, A. Consolaro: None declared, V. Panaviene: None declared, V. Stanevicha: None declared, M. Trachana Grant/research support from: Abbvie, Novartis, Pfizer, Consultant for: Novartis, Pfizer, Roche, Speakers bureau: Novartis, Pfizer, Roche, C. Ailioaie: None declared, P. Quartier: None declared, F. De Benedetti: None declared, E. Tsitsami: None declared, B. Flato: None declared, P. Dolezalova Grant/research support from: Novartis, Speakers bureau: Novartis, Pfizer, Roche, Abbvie, T. Constantin Speakers bureau: Pfizer, Abbvie, Novartis, Roche, Bristol-Myers Squibb, T. Herlin: None declared, S. Kamphuis: None declared, S. Sawhney: None declared, D. Maritsi: None declared, V. Vargova: None declared, L. Villa: None declared, C. Pallotti: None declared, A. Ravelli Consultant for: Roche, Speakers bureau: Abbvie, Novartis, Pfizer, A. Martini Shareholder of: Abbott, BMS, "Francesco Angelini", GlaxoSmithKline (GSK), Hoffman-La Roche, Italfarmaco, Janssen, Novartis, Pfizer, Sanofi Aventis, Schwarz Biosciences, Sobi, Xoma, Wyeth. The Gaslini Hospital, which is the public Hospital where I work as full time public employee, has received contributions from the industries mentioned in this section. This money has been reinvested for the research activities of the hospital in a fully independent manners besides any committment with third parties., Consultant for: Honoraria for consultancy: Abbott, AbbVie, Amgen, Biogenidec, Astellas, Alter, AstraZeneca, Boehringer, BMS, CD-Pharma, Celgene, CrescendoBio, EMD Serono, Hoffman-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, Sanofi Aventis, Servier, Vertex., Speakers bureau: Honoraria for speaker's bureau from: Abbvie, Medimmune, Novartis, Roche, Takeda, N. Wulffraat: None declared, N. Ruperto Shareholder of: Abbott, BMS, "Francesco Angelini", GlaxoSmithKline (GSK), Hoffman-La Roche, Italfarmaco, Janssen, Novartis, Pfizer, Sanofi Aventis, Schwarz Biosciences, Sobi, Xoma, Wyeth. The Gaslini Hospital, which is the public Hospital where I work as full time public employee, has received contributions from the industries mentioned in this section. This money has been reinvested for the research activities of the hospital in a fully independent manners besides any committment with third parties., Consultant for: Honoraria for consultancy: Abbott, AbbVie, Amgen, Biogenidec, Astellas, Alter, AstraZeneca, Boehringer, BMS, CD-Pharma, Celgene, CrescendoBio, EMD Serono, Hoffman-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, Sanofi Aventis, Servier, Takeda, Vertex., Speakers bureau: Honoraria for bureau speaker: Abbott, AbbVie, Amgen, Biogenidec, Astellas, BMS, CD-Pharma, Hoffman-La Roche, Pfizer